Heritabilitas dan Harapan Kemajuan Genetik Beberapa Karakter Kuantitatif Populasi Galur F4 Kedelai Hasil Persilangan - Hakim, Lukman; Suyamto, Suyamto (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
The F4 soybean progenies derived from two cross combinations and their three parent varieties were evaluated for their heritability and expected genetic advances of quantitative traits, at Ngale Experimental Station, Ngawi, East Java during the dry season of 2009. The experiment was arranged in a randomized block design with three replications. Seeds of each F4 progenies and their parents were sown in two rows of 4.5 m length of plots with a 40 cm x 15 cm plant spacing, two plants/hill. Plant population of each F4 progenies and their parents were 120 plants in each replication. Among the characters observed, seed yield per plant, number of pods per plant, and days to maturity had the highest coefficient of variability, with the means of 50.4%, 47.4% and 43.9%, respectively. Number of branches, number of nodes per plant and days to flowering had the lowest coefficient of variability, and the means were 14.0%, 14.3% and 17.2%, respectively. The heritability estimates of the 8 quantitative characters ranged from 19.4% to 55.9%. Plant height, number of pods per plant, and days to maturity had the highest heritability estimates for the two crosses, namely 55.9%, 51.5% and 41.2%, respectively. The mean heritability estimate for seed yield per plant and number of nodes per plant were the lowest, namely 19.7% and 19.4%, respectively. Based on the F4 data, selection on the number of pods per plant had the highest expected genetic advances of 41.8%, followed by the days to maturity (40.7%) and the plant height (38.0%). The mean of expected genetic advances for the number of branches and the number of nodes per plant were the lowest, namely 13.7% and 13.5%, respectively. In relation to the grain yield, the mean heritability estimate for seed yield per plant was low (19.7%). However, considerable genetic variability (50.4%) and genetic advances (35.8%) was present on the seed yield per plant.